Study of Glycated Hemoglobin (Hba1C) Levels in Iraqi Pregnant Women with Non-Diabetic Iron Deficiency Anemia (World Journal of Experimental Biosciences, 2017)
The objective of the present study was to determine whether the Glycosylated hemoglobin (HbA1c) levels were increased in some non-diabetic pathological states especially Iron deficiency anemia. This study conducted on 52 non diabetic pregnant women sorrow from iron deficiency anemia and 30 non diabetic healthy pregnant women were enrolled to serve as a control group. The patient’s data released from National Hematology Center, Baghdad, Iraq for about five months and the required tests were examined under medical expert in this field in order to ensure the accuracy for the demanding tests. The ages of patients were ranged from 20 to 45 years old. Our results showed a significant difference (P < 0.005) in case of Hba1C levels between iron deficiency anemia group and control group. Same results was found in all blood and biochemical tests which included in this study (serum ferritin, serum iron, serum total iron binding capacity, Hemoglobin level and Red blood cell count).